HUBUNGAN EFIKASI DIRI KELUARGA DENGAN FREKUENSI KEKAMBUHAN PASIEN SKIZOFRENIA SELAMA PANDEMI COVID-19 DI RSJ PROVINSI BALI - Diastuti, Ni Nyoman Parayoni; Swedarma, Kadek Eka; Antari, Gusti Ayu Ary (Coping: Community of Publishing in Nursing; Vol 11 No 6 (2023): Desember 2023DO - 10.24843/coping.2023.v11.i06.p01, 2024)
Schizophrenic patients often experience relapses even during the current Covid-19 pandemic. Factors that influence come from the family as a caregiver. Caregivers need self-efficacy to carry out good care. This research aims to determine the relationship between family’s self-efficacy with the frequency of relapse of schizophrenic patients during the Covid-19 pandemic. This study used a correlational description method with a cross-sectional design. Data collection was carried out directly at the Emergency Room starting on April 23, 2022, until May 25, 2022. The number of respondents involved was 75 families who came to the ER of the RSJ Provinsi Bali using the incidental sampling technique. The statistical test used is Spearman rank. The results showed that most of the respondents had family self-efficacy in the high category (56%) and the recurrence frequency of patients in the non-relapse category (38,7%). The results of the analysis found that there was a relationship between self-efficacy with the frequency of recurrence of schizophrenia patients during the COVID-19 pandemic at the RSJ Provinsi Bali with a negative direction and weak correlation strength (r = -0,367; p = 0,001; ? = 0,05).